Using Incentives and Reminders to Increase Fruit and Vegetable Intake among Wisconsin Elmentary School Students - Jamelske, Amber; Reinhold, Bryan; Reinhold, Kevin; Reinke, Elizabeth (My University, 2010)
The United States Department of Agriculture (USDA) initiated the Fresh Fruit and Vegetable Program (FFVP) in 2002. The FFVP provides funding for students from selected schools to receive a free fruit or vegetable (FV) snack 3-4 days a week for an academic year. In this study, we have extended our previous research to examine two methods of expanding the reach of the FFVP beyond the access to free FV provided as snacks in the classroom. First, we analyzed data from a FV coupon experiment conducted in two West-Central Wisconsin elementary schools as part of our 2008-09 FFVP. Second, we looked at detailed data tracking the daily FV snack behavior of students from a different West-Central Wisconsin elementary school as part of our evaluation of the 2009-10 FFVP.
Color poster with text and graphs.
Keywords: Fresh Fruit and Vegetable Program (Wis.); Nutrition--Study and teaching (Elementary); School children--Nutrition--Wisconsin; Food habits--Psychological aspects; Posters